Unusual Sequence of Events in a Case of Takotsubo Syndrome. (13th December 2018) - Henriquez, C.; Landau, R.; Sabharwal, N.; Rodriguez, D.; Virparia, V.; Sadiq, A.; Shani, J.
Abstract : A 73-year-old female with multiple comorbidities including coronary artery disease was admitted for an elective PCI of a lesion detected in the RCA. On the day of the planned PCI, shortly after right femoral artery cannulation, the patient developed a sudden complete heart block requiring the administration atropine and insertion of a temporary pacemaker. Concomitantly, the patient developed acute pulmonary edema, hypotension, and hypoxia requiring intubation for mechanical ventilation. Vasopressors were administered. A coronary angiogram showed patent left and right coronary arteries, unchanged when compared to the previous angiogram. An echocardiogram performed in the cardiac catheterization lab revealed global hypokinesis of the left and right ventricles, with severe LV systolic dysfunction (E F < 20 % ). Following an insertion of an intra-aortic balloon pump, the patient was transferred to the CICU. A repeat echocardiogram in the CICU two hours later revealed a classical echocardiographic presentation of Takotsubo syndrome, apical hypokinesis. By the next morning the patient's hemodynamic status significantly improved, the balloon pump was removed, and vasopressors were discontinued. Another echocardiogram was performed 24 hours after the event occurred and revealed a marked improvement in LV systolic function (EF 60%), with complete resolution of apical and septal wall motion abnormalities. Three days after the event, the patient was successfully discharged and asymptomatic at two-month follow-up. This case illustrates an atypical presentation of Takotsubo syndrome that was witnessed from onset to its complete resolution during the patient's hospital stay.